Good news on public restriction and stock prices in Indonesia - Valentine Siagian (MBR (Management and Business Review), 2022)
his paper aims to investigate the impact that the news has on the public's ability to restrict stock prices on the Indonesia Stock Market. There are a total of 18,824 firm-day observations derived from 724 different firms that are listed, and that are observed 25 trading days. In order to validate the data, panel data regression was utilized, and additional regression on each industry was carried out. According to the findings of this paper, the number of specimens that were announced today does, in fact, affect the closed price on the following day. There is a correlation between the total number of cases recovered and stock prices. From an empirical standpoint, even a higher recovered case was unable to provide assurance that the following day's stock prices would remain stable.